2020
DOI: 10.1155/2020/8276392
|View full text |Cite
|
Sign up to set email alerts
|

Multiagent Collaborative Governance for Targeted Poverty Alleviation from the Perspective of Stakeholders

Abstract: As a social problem involving a wide range of objects, targeted poverty alleviation governance needs to clearly define stakeholders and identify their behaviour choices, so as to seek a multiagent collaborative governance strategy, and strive to jointly promote the realization of a targeted poverty alleviation goals in an atmosphere to win-win cooperation and benefit sharing. By constructing a three-subject evolutionary game model of local government, social organization, and poverty group in the process of ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Collaborative governance needs to be done as an effort to overcome poverty problems (Zhang et al, 2020). The results of the study indicate that the collaboration process in empowerment that has been carried out so far for the relocation community in Rawabebek flats has only touched the instrumental aspect and has not touched the substantial aspect.…”
Section: Resultsmentioning
confidence: 93%
“…Collaborative governance needs to be done as an effort to overcome poverty problems (Zhang et al, 2020). The results of the study indicate that the collaboration process in empowerment that has been carried out so far for the relocation community in Rawabebek flats has only touched the instrumental aspect and has not touched the substantial aspect.…”
Section: Resultsmentioning
confidence: 93%
“…erefore, a full model (Model 3) was established, in which the slopes of the above five variables and intercept were treated as random and were allowed to vary across villages. Following the "t-to-enter" method [27], five variables (village size, poverty incidence, economic level, distance to county road, and distance to river) with the largest t-values at the village-level were added to the full model (results not shown). A comparison of the original variance from Model 2 and the conditional variance from Model 3 revealed that the village-level variables had impacts at different variance levels.…”
Section: Results Of the Hierarchical Linear Models (Hlms)mentioning
confidence: 99%
“…Several studies conducted on rural China have shed light on the existing state of affairs and spatial distribution of poor households' income levels and the associated driving mechanisms [24][25][26][27]. As town-and village-level data are not available, most of these studies targeted the province, city, or county levels.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the premise of bounded rationality and dynamic evolution of the evolutionary game theory comparatively abides by the behaviour rules and decision-making characteristics of local governments, functional departments, and end users. For instance, Zhang and Li studied multiagent collaborative governance for targeted poverty alleviation based on the evolutionary game analysis framework [36].…”
Section: Literature Reviewmentioning
confidence: 99%